2013
DOI: 10.1097/ta.0b013e31827880a8
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of 24/7 intensivist presence in the SICU

Abstract: Care management study, level IV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 21 publications
0
15
0
Order By: Relevance
“…Further the study demonstrated nighttime staffing with an attending non-intensivist was associated with a slightly longer duration of mechanical ventilation (25). A similar study carried out in a surgical ICU population did not improve SICU morbidity or mortality but was associated with decreased blood product use and fewer radiological imaging studies (26). In a cluster randomized trial conducted in North America involving intensivist staffing, the outcomes in medical ICU patients were not worse despite a lower continuity of care by the intensivist, the outcomes in medical ICU patients were not worse and work schedules of intensivists receiving weekend breaks were better for the physicians (27).…”
Section: Accepted Manuscriptmentioning
confidence: 78%
“…Further the study demonstrated nighttime staffing with an attending non-intensivist was associated with a slightly longer duration of mechanical ventilation (25). A similar study carried out in a surgical ICU population did not improve SICU morbidity or mortality but was associated with decreased blood product use and fewer radiological imaging studies (26). In a cluster randomized trial conducted in North America involving intensivist staffing, the outcomes in medical ICU patients were not worse despite a lower continuity of care by the intensivist, the outcomes in medical ICU patients were not worse and work schedules of intensivists receiving weekend breaks were better for the physicians (27).…”
Section: Accepted Manuscriptmentioning
confidence: 78%
“…While it has been shown that RVU generation is higher for surgeons who spend time providing critical care than those who do not, this was only found to be true in groups where the remaining members are clinically productive and billing diagnoses are vast beyond the operative diagnosis where critical care billing or E/M can be applied 18 . This model implies that there should be pooling of the group’s RVUs to increase overall reflection of productivity, but this model takes away each individual’s contribution and makes the individual dependent on group effort.…”
Section: Discussionmentioning
confidence: 97%
“…We performed two independent subgroup analysis to investigate the effect of country of study and the effect of a routine onsite intensivist cover overnight. between the presence of a night-time ICU doctor and patient survival (45)(46)(47), and a randomized control trial of nighttime intensivist staffing was not associated with either ICU/hospital mortality or length of stay (48). Two large databases across 49 American ICUs demonstrate that night-time ICU doctor staffing in addition to a high intensity daytime staffing did not reduce ICU mortality (49).…”
Section: Discussionmentioning
confidence: 99%